Pengaruh Model Problem Based Learning Terhadap Hasil Belajar Matematika Siswa SD - Anisa Nur Fadilah; Adisel Adisel; Fatrimia Santri Syafri; Suryati Suryati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
The purpose of this study was to determine the effect of problem-based learning on mathematics learning outcomes for fourth grade students of SD Negeri 28 Kaur. The sampling technique in this study used a saturated sample technique where all students were sampled in the study. The researcher took class IV to serve as the research sample, which amounted to 15 students as the experimental class. The research design used in this study was only one group, so it did not require a control class. Analysis of data testing using the t test, can be seen through the normality test that was carried out previously with a significance value of 0.200> 0.05 and it was stated that the data were normally distributed. Furthermore, by using the t-test, the students' mathematics learning outcomes got an average pretest score of 67.00 and an average posttest score of 80.40 with a descriptive conclusion that there were differences in student learning outcomes. Based on the results of the Paired Sample T-Test test output, it is known that the significance value (Sig.) (2-tailed) is 0.000. Provided that if the significance value is 0.000 <0.05, then HO is rejected and Ha is accepted. So it can be concluded that there is an influence in the use of problem-based learning models in fourth grade students of SD Negeri 28 Kaur. Keywords: Influence, Problem Based Learning Model, Mathematics